The Tradition of the Gospel Christians: A Reconstruction of the Practice of Biblical Interpretation - Puzynin, Andrey (Bogoslovskie razmyšlenija, 2012)
This thesis explores the practice of biblical interpretation in the post-Soviet tradition of the Gospel Christians that has its origins in the ministry of the Victorian revivalist preacher Lord Radstock in St. Petersburg in the 1870s. Attempting to resolve the current interpretive impasse, this study provides a diachronic descriptive analysis of the practice. The analysis reveals that the major causes of the contemporary crisis pertain to the radical shift that took place in the tradition's prac1tice after the collapse of the Soviet Union. The inductive Bible study method was introduced by Western educators and presented as the only correct methodology, thereby rendering the former pre1critical interpretive practices as unscientific and wrong. Building on the discoveries of historical analysis, the thesis suggests a new paradigm for biblical interpretation which is tradition1 continuous. Following the trajectory of the Evangelical tradition in the Post1Soviet context, a trajectory which relies on Western thought, the thesis adopts a theological differential integral hermeneutics. This interpretive strategy takes into account three levels of interpretation: the author's intention, the literal meaning, and the representational content of a text in the history of its interpretation. The interpreter is expected to publicly justify his or her interpretive decisions in light of the community's historical self1identity, its core values, and its concept of good.